PENERAPAN ASAS ITIKAD BAIK DALAM PERJANJIAN HUTANG PIUTANG (STUDI KASUS PERKARA NOMOR 16/PDT.G/2014/PN.PRM) - Mahliyanti Adelia Warman; Dewiwarman (Fakultas Hukum Universitas Islam Indragiri, 2022)
Good faith has been the benchmark for each party in conducting in agreement, based on honesty, decency and suitability, even towards an agreement regarding debt. In this civil case, each party have agreed to carry out a verbal pact in order to purchase clothes with a value of Rp. 89.000.000,- (eighty nine million rupiahs) using debts as a method or purchase, and will be paid back in a few days. When the party fails to pay back the debt at a given amount af time and has not tried to get in touch with in the span of 5 (five) years, wich showed the debter lacked on decent morals as the payments had not been paid off and not even a single installment werw paid. Based on the case above, the problem analysed about the application off good faith on agreement of a debt and the judge has a given consideration to stipulated of the decision toward on case number 16/Pdt.G/2014/PN.PRM. This research was juridical normative in which the research itself conducted descriptively, the data processes were done by editing and data collected was analysed by qualitative method. From said case, it can be concluded that the agreement of repayment of debts had not been met because the debter clearly had not paid back and the judge had not gave decision based on the requirements.